A super flexible and custom-shaped graphene heater. Issue 38 (20th July 2017) - Zhang, Tian-Yu; Zhao, Hai-Ming; Wang, Dan-Yang; Wang, Qian; Pang, Yu; Deng, Ning-Qin; Cao, Hui-Wen; Yang, Yi; Ren, Tian-Ling
Abstract : In this paper, we fabricate a graphene film heater through laser reduction on graphene oxide, which is a two-step process. Abstract : In this paper, we fabricate a graphene film heater through laser reduction on graphene oxide, which is a two-step process. The electrothermal performance of the graphene heater can be adjusted by the laser energy density. While the applied voltage is 18 V, the graphene heater reaches a steady-state temperature of 247.3 °C within 20 s. After the graphene heater is folded in half 100 times, its output temperature remains to be precisely controlled by the input power and the temperature distribution is uniform. In addition, the flexibility of the graphene heater is superior to a heater based on a commercial indium tin oxide film. It's worth noting that the graphene heater can be fabricated with desired shapes directly and easily, which is rare among the reported film heaters. In consideration of the high performance of the graphene film heater, we demonstrate its three application scenarios: portable warmers applied in medical infusion apparatus, flexible custom-shaped heaters for special requirements and displays.